Protective effect of the curcumin-baicalein combination against macrovascular changes in diabetic angiopathy - Wang, Chenxiang; Sun, Yibin; Liu, Wenjing; Liu, Yang; Afzal, Sualiha; Grover, Jahnavi; Chang, Dennis; Münch, Gerald; Li, Chun Guang; Lin, Shiling; Chen, Jianyu; Zhang, Yiping; et al. (Frontiers in Endocrinology, 2022)
Endothelial dysfunction is an early pathological event in diabetic angiopathy which is the most common complication of diabetes. This study aims to investigate the individual and combined actions of Curcumin (Cur) and Baicalein (Bai) in protecting vascular function. The cellular protective effects of Cur, Bai and Cur+Bai (1:1, w/w) were tested in H2O2 (2.5 mM) impaired EA. hy926 cells. Wistar rats were treated with vehicle control as the control group, Goto-Kakizaki rats (n=5 in each group) were treated with vehicle control (model group), Cur (150 mg/kg), Bai (150 mg/kg), or Cur+Bai (75 mg/kg Cur + 75 mg/kg Bai, OG) for 4 weeks after a four-week high-fat diet to investigate the changes on blood vessel against diabetic angiopathy. Our results showed that Cur+Bai synergistically restored endothelial cell survival and exhibited greater effects on lowering the fasting blood glucose and blood lipids in rats compared to individual compounds. Cur+Bai repaired the blood vessel structure in the aortic arch and mid-thoracic aorta. The network pharmacology analysis showed that Nrf2 and MAPKp38-JNK kinase were highly relevant to the multi-targeted action of Cur+Bai which has been confirmed in the in vitro and in vivo studies. In conclusion, Cur+Bai demonstrated an enhanced activity in attenuating endothelial dysfunction against oxidative damage and effectively protected vascular function in diabetic angiopathy rats.